Pengaruh Pembelajaran Kitab Aqidatul Awam dalam Penanaman Nilai-Nilai Tauhid Santri di Madrasah Diniyah Tanwirul Qulub Lamongan - Azis Joko Pamungkas; Syuhada; Siti Latifatus Sun’iyah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The degree of quality of an individual's religion is significantly influenced by the value of monotheistic. In the life of a Muslim, this is undeniable; students are not an exception. Many students nowadays ignore religious issues, which obviously have a significant influence on their future lives. In order to address this, Islamic boarding schools use Sayyid Ahmad Marzuqi's book Aqidatul Awam to teach students the importance of monotheism in a more thorough manner. Aqidatul Awam's book This book serves as a foundation for understanding the importance of monotheism for lay people. This study aims to investigate further how the value of monotheistic may raise a student's degree of faith, demonstrating that real monotheism can result in a better life than the one before it. Researchers employed qualitative research techniques in its implementation. A more sophisticated approach is the qualitative research method. Prioritize meaning and process over outcomes. In order to gather data, the researcher employed the triangulation methodology, which combines documentation, interviewing, and observation methods. The kind of strategy The Tanwirul Qulub Islamic Boarding School served as the site of the case study research project. Inductive data analysis, which adheres to Miles and Huberman's ideas, is used in this study. The outcomes show that the book Aqidatul Awam's teachings on the need for monotheism may strengthen a person's faith, which in turn has a significant impact on a student's belief in divinity, particularly at Tanwirul Qulub Islamic Boarding School in Lamongan.